Enhancing bone tissue engineering using iron nanoparticles and magnetic fields: A focus on cytomechanics and angiogenesis in the chicken egg chorioallantoic membrane model - Santosh Yamanappa Nelogi; Anand Kumar Patil; Ramesh Chowdhary (Wolters Kluwer Medknow Publications, 2024)
Aim: To evaluate the potential of iron nanoparticles (FeNPs) in conjunction with magnetic fields (MFs) to enhance osteoblast cytomechanics, promote cell homing, bone development activity, and antibacterial capabilities, and to assess their in vivo angiogenic viability using the chicken egg chorioallantoic membrane (CAM) model. Settings and Design: Experimental study conducted in a laboratory setting to investigate the effects of FeNPs and MFs on osteoblast cells and angiogenesis using a custom titanium (Ti) substrate coated with FeNPs. Materials and Methods: A custom titanium (Ti) was coated with FeNPs. Evaluations were conducted to analyze the antibacterial properties, cell adhesion, durability, physical characteristics, and nanoparticle absorption associated with FeNPs. Cell physical characteristics were assessed using protein markers, and microscopy, CAM model, was used to quantify blood vessel formation and morphology to assess the FeNP-coated Ti's angiogenic potential. This in vivo study provided critical insights into tissue response and regenerative properties for biomedical applications. Statistical Analysis: Statistical analysis was performed using appropriate tests to compare experimental groups and controls. Significance was determined at P < 0.05. Results: FeNPs and MFs notably improved osteoblast cell mechanical properties facilitated the growth and formation of new blood vessels and bone tissue and promoted cell migration to targeted sites. In the group treated with FeNPs and exposed to MFs, there was a significant increase in vessel percentage area (76.03%) compared to control groups (58.11%), along with enhanced mineralization and robust antibacterial effects (P < 0.05). Conclusion: The study highlights the promising potential of FeNPs in fostering the growth of new blood vessels, promoting the formation of bone tissue, and facilitating targeted cell migration. These findings underscore the importance of further investigating the mechanical traits of FeNPs, as they could significantly advance the development of effective bone tissue engineering techniques, ultimately enhancing clinical outcomes in the field.